SUPLEMENTASI EKSTRAK DAUN KELOR (Moringa oleifera L.) TERHADAP ANEMIA DEFISIENSI BESI: ARTIKEL REVIEW - Satria, Dzakiyyah Shoofina Jasmine; Triyandi, Ramadhan; Iqbal, Muhammad; Andrifianie, Femmy (Medula, 2024)
Iron is an important component of hemoglobin. The function of iron, which is as a source of energy for muscles so that it can affect physical endurance and the ability to work in adolescents. Iron deficiency can lead to hematological disorders of anemia. Anemia is a body condition in which the number of red blood cells and oxygen transport capacity is insufficient to meet the physiological needs of the body. Moringa leaves can be used as a substitute for iron tablets, because Moringa leaf powder contains 28 mg of iron. The method used in this writing, is literature review by collecting several research articles. This literature source search uses literature research sources in the form of google scholar and Pubmed. The inclusion criteria from the search, namely research articles using Indonesian and English, articles published within the last 10 years (2013-2023), and discussing the topic of moringa oleifera and anemia. The results of this literature search can be concluded that Moringa oleifera supplementation significantly increases serum iron levels.